2016
DOI: 10.1016/j.canlet.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA identified by targeted sequencing in advanced-stage non-small cell lung cancer patients

Abstract: Non-small cell lung cancers (NSCLC) have unique mutation patterns, and some of these mutations may be used to predict prognosis or guide patient treatment. Mutation profiling before and during treatment often requires repeated tumor biopsies, which is not always possible. Recently, cell-free, circulating tumor DNA (ctDNA) isolated from blood plasma has been shown to contain genetic mutations representative of those found in the primary tumor tissue DNA (tDNA), and these samples can readily be obtained using no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 37 publications
1
85
2
Order By: Relevance
“…For example, in a proof‐of‐concept study, the FDA‐approved Oncomine targeted sequencing kit demonstrated a sensitivity of only 77% for the detection of sensitizing EGFR mutations in cfDNA of NSCLC patients . Similar results, with an overall concordance of 76% between tumor tissue and cfDNA, were reported for the AmpliSeq Cancer Panel . To overcome these limitations, more sensitive targeted and genome‐wide sequencing approaches with improved error suppression rates have been developed .…”
Section: Different Methods For Mutation Detection In Routine Diagnosticsmentioning
confidence: 71%
“…For example, in a proof‐of‐concept study, the FDA‐approved Oncomine targeted sequencing kit demonstrated a sensitivity of only 77% for the detection of sensitizing EGFR mutations in cfDNA of NSCLC patients . Similar results, with an overall concordance of 76% between tumor tissue and cfDNA, were reported for the AmpliSeq Cancer Panel . To overcome these limitations, more sensitive targeted and genome‐wide sequencing approaches with improved error suppression rates have been developed .…”
Section: Different Methods For Mutation Detection In Routine Diagnosticsmentioning
confidence: 71%
“…Xu et al. () reported a consistency of 76.2% for next‐generation sequencing technology in detecting gene mutation in tissue samples and cell‐free DNA of paired blood samples in advanced lung cancer patients. We found a consistency of 76.2% for TP53 and 95.24% for BRCA1 in circulating tumor‐free DNA and tumor tissue DNA, suggesting that cell‐free DNA and circulating tumor cells could offer a ready and convenient source for liquid biopsy for detection of biomarkers that could be used to monitor disease development and predict prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, circulating cell‐free DNA and circulating tumor cells have been found to offer a ready and convenient source for liquid biopsy (Xu et al., ); genetic alterations found in liquid biopsy specimens are identical to those in primary cancer tissues. Murtaza et al.…”
Section: Introductionmentioning
confidence: 99%
“…ctDNA can be applied in detection of point mutations, copy number variation (CNV), rearrangements, microsatellite instability (MSI), loss of heterozygosity (LOH) and DNA methylation . Multiple studies have shown that the mutation profile detected by ctDNA has a good concordance with paired tumor tissues, with 70% in lung cancer and 39%–55% in colorectal and rectal cancer . ctDNA analysis also facilitates the assessment of intra‐patient multiple drug resistance mechanisms caused by tumor heterogeneity in non‐small cell lung cancer (NSCLC) .…”
mentioning
confidence: 99%